THEORETICAL FRAMEWORK FOR USING RESOURCE BASED VIEW IN THE ANALYSIS OF SME INNOVATIONS - Ilona Baumane-Vitolina; Igo Cals (European Scientific Journal, ESJ, 2014)
The objective of this paper is to present a Resource based view of a firm as a valid conceptual framework for the analysis of SME innovativeness. This paper may serve future studies aiming at devising a methodology for estimation of the connection between resource categories of various enterprises and the implementation of innovation and growth in small and medium enterprises. Authors provide a thorough literature analysis and propose their own categorization of firm’s resources. Morover, a critical review of innovation indicators and their congruency with research aims is provided within the paper.